Health Professional's Knowledge and Attitude Regarding Adolescent Pregnancy Care in Primary Health Care Centers in Erbil City - Srwa Abdulrahman Mustafa; Hamdia Ahmad Mirkhan (Hawler Medical University, 2020)
Background and objectives: The World Health Organization defines adolescent pregnancy as pregnancy in which the mother is under the age of 20 at the time the pregnancy ends. About 16 million girls ageing between 15 and 19 years give birth every year. The study aimed to assess the level of knowledge and attitude among nurses and physicians in Erbil Primary Health Care Centers regarding adolescent pregnancy care and comparing them. Methods: A quantitative; descriptive cross-sectional study was conducted in maternal and child health care units at twenty-three Primary Health Care Centers in Erbil city, between November 15th , 2018 and November 15th, 2019. Non-probability, Convenience sampling technique was used for selecting sample which includes 95 from the total of 100 health professionals. Data was collected through interview (face to face) by using questionnaire form which was designed by the investigator. Data were analyzed using the Chi-square test, Fisher's exact test. Results: Health professionals mean age + SD was 41.95 + 8.40 years, ranging from 27 to 62 years. The median was 42 years. Less than half (42.1%) of the sample were nurses, and the rest were physicians of different specialties. The highest percentage of the nurse's knowledge and attitude were in medium level (42.5% and 47.5%, respectively). The highest percentage of physician's knowledge and attitude were in high level (58.3% and 65.5% respectively). There were significant difference between them regarding their knowledge (p = 0.32) and attitude (p = 0.006). Conclusions: Health professionals working in maternal and child health care units need improving their knowledge and attitude regarding adolescent pregnancy care. Nurses need more information and training sessions regarding that.